GIS-MCDM Approach to Determine Forest Plantation Areas in U-tapao River Basin in Songkhla, Thailand - Ali, Dilawer; Batool, Shahida; Techato, Kuaanan; Gyawali, Saroj; Suklueng, Montri (International Journal of Integrated Engineering, 2020)
Land suitability assessment is indispensable for the successful forest land use development. This will provide a rational basis to accomplish the land use decisions. Forest land degradation owing to distinct reasons (rapid urbanization, transformation to the agricultural land) has become a matter of great concern. Therefore, this research aim was to determine the forest plantation area in U-tapao river basin (URB), Southern Thailand. Multicriteria decision making (MCDM) technique was used in Geographic Information System (GIS) environment to find as well as to validate a suitable land for forest planation in the study area considering two main factors i.e. bio-physical and socio-economic. This study found that out of total area of the URB (2305 km2), approximately 59.66 percent (1375.2 km2) is highly suitable for forest plantation. This study may assist the future researchers and forest policymakers to take measures against the forest land degradation